PENINGKATAN POTENSI WISATA LA BOLONTIO TERHADAP PENGEMBANGAN KEMAJUAN PENDAPATAN PEMERINTAH DESA DI SIOMPU KABUPATEN BUTON SELATAN - Wa Nur Fida; Muh. Rizal Ardiansyah Putra; Amrin (Jurnal Cakrawala Ilmiah, 2023)
One of the potentials that can be increased to Village Original Income (PADes) for villages in Indonesia is the tourism sector. Touring in the village has become a separate choice for tourists. Tourists who like tourist attractions in the village are not only interested in its natural beauty but also interact with local people. Tourist attractions provided by various villages in Siompu are one of the goals of the village government in increasing village income as a form of village development and progress. The government manages various places that are considered to be developed as a source of extraordinary income and progress in managing villages and can compete in the world of tourism which shows the natural beauty that exists in their villages as seen in Siompu, one of the islands or Kaimbula Village which has natural beauty and the ocean. The village government takes advantage of the beauty of the coast of the island in the village of Kaimbulawa as a form of developing tourism potential in advancing the village and being able to compete with other islands. kaimula village is located on a plateau and the lowland is the ocean so the location of where they live requires them to live in the highlands. However, the beauty of the coast which is quite stunning is utilized by the village government as a form of economic income by making Labolontio a tourist spot. The recreation area is also a historical place called Labolontio which is very famous in Buton Island. What makes this tourist spot interesting to visit is not only the beauty of the beach and nature, but also historical places that can be visited and a variety of cultures that attract visitors or tourists.